THE CONTRIBUTION OF PIBID TO THE TRAINING OF THE ACADEMIC SCHOLARSHIPS FROM THE SCHOOL JORGE EWALDO KOCH (Fiep Bulletin - online, 2015)
This article investigates the contribution of the Institutional Program Initiation to Teaching Scholarship - PIBID for physical education students training, University Feevale's teachingdegree mode, at the Municipal Elementary School Ewaldo George Koch, in Novo Hamburgo - RS. It has been developed through a qualitative descriptive study. The approach used for data collection represents an open questionnaire to academic scholar part of this program in the second semester of 2013. Results point to the importance of PIBID to students, highlighting experiences, contributions, realities and situations which the program provides; as well as the ability to plan, perform and produce scientifically, contemplating all the duties of teaching with the aid of an advisor. In conclusion, the program contributes to general academic training, which can unite the theory learned in the undergraduate teaching practice performed in the program, and reflect and raise the awareness about the importance of teachers role in society.
Keywords: Training; Physical Education; Licentiate; PIBID.